Utilization of WEB based Technology Through the Sepak Takraw Sports Match Administration System Application - Akram Muhibulloh Bangko; Amir Supriadi; Budi Valianto (UNIB Press, 2023)
This research generally aims to produce a Web based match administration system application product. This study uses the development model from Borg and Gall which is adapted into a simple model, namely: determining research potential and problems, gathering information, needs analysis, product design and design validation, media expert testing, IT expert testing, takraw expert testing, trials small group, revise the results trials, trials large group, revise the results trials, final product development. The research results show from the results. Phase I trials were conducted on 15 sports science faculty students. Phase II trials were conducted on 30 people athlete and takraw administrators in North Sumatra who are classified as active. Of the 15 small group trial samples with a total score of 3.80 divided by the maximum score resulting in a presentation of 79.45% with the criteria Worth it. The results of large-scale trial data (stage II) against athlete and takraw administrators in North Sumatra who are classified as active, it can be seen that with an average percentage of 92.65% in the category So Worth it. The researcher concludes that the application product for the administration of a web based Sepak Takraw sports match is already worth using the foresee match administration system. The use of application products is a new way for stakeholder and takraw sports activists in North Sumatra in carrying out drawing matches and when you want to chart matches.